Recent Advances in Transition-Metal-Catalyzed (4+3)-Cycloadditions - Lam, Heather; Lautens, Mark (Synthesis, 2020)
A (4+3)-cycloaddition combines a four-atom synthon and three-atom synthon to form seven-membered rings. In the past decade, many improvements have been made to this class of cycloaddition, including excellent diastereo- and enantioselectivities, both intra- and intermolecularly. Through the strategic use of transition-metal catalysts, acids, bases, and organocatalysts, it is possible to perform the cycloaddition on a variety of substrates, generating novel seven-membered rings. With these advances, (4+3)-cycloaddition has also been applied to the synthesis of biologically relevant compounds and natural products. We exclude the cycloadditions of cyclic dienes such as furan, pyrrole, cyclohexadiene or cyclopentadiene as Chiu, Harmata, Mascareñas and others have recently published thorough reviews on that topic. We will however discuss the recent additions (2009–2020) to the literature for the (4+3)-cycloadditions involving other types of four-atom synthons.1 Introduction2 Rhodium2.1 Cyclopropanation/Cope Rearrangement2.2 C–H activation3 Gold, Silver4 Copper5 Palladium, Platinum, Iridium6 Dual-Activation7 Conclusion
Keywords: (4+3)-cycloaddition; annulation; transition-metal catalysis